Ancient Egyptian kingship - Baines, John (Annuaire, 2014)
The aim of this course was to review the study of Egyptian kingship as the central institution of society and cosmos, with a focus on how the king related to court institutions surrounding him, as well as how his role in relation to the gods was projected and is now interpreted. The presentation was partly chronological, with the first lecture considering origins and the last surveying the institution in the long term. The nearly four millennia from which kingship is attested can only be sampled. Much of the evidence treated was iconographic rather than textual. One aim was to bring out the importance of visual forms for the performance, display, and meaning of kingship, in a mode that probably spoke more eloquently to many people than texts did. Another focus was the sophistication of the sources (The course was delivered in French ; the French titles of the lectures are retained here.)